Xylanase supplementation of pelleted wheat-based diets increases growth efficiency and apparent metabolizable energy and decreases viscosity of intestinal contents in broilers - Brad Gorenz; Vanessa Iseri; Jon Rubach; Ryan N. Dilger (Poultry Science, 2022)
ABSTRACT: This study was designed to test graded supplementation of a thermostable xylanase in pelleted, wheat-based diets fed to broiler chickens over a 28-d period. A total of 600 Ross 708 male broilers were allotted to 1 of 5 dietary treatments: positive control (PC), negative control (NC; 125 kcal of AME/kg diet reduction relative to PC), and NC supplemented with 10, 15, or 30 g/ton of xylanase. Wheat-soybean meal-based diets were pelleted and fed in 2 feeding phases (14-d each). Study outcomes included growth performance, AME, and ileal digesta viscosity with 20 battery cages of 6 birds per treatment. Data were analyzed by 1-way ANOVA along with estimation of Pearson correlation coefficients. Whereas no difference between NC and PC was observed for BW gain, NC birds exhibited increased (P < 0.05) feed intake during each feeding phase and overall, which caused improvements (P < 0.05) in feed conversion ratio (FCR) for PC vs. NC birds. The analyzed AME of PC birds was 112 kcal/kg of diet greater (P < 0.05) than for NC birds, though no differences in digesta viscosity were observed. Xylanase supplementation of the NC diet at 15 or 30 g/ton elicited overall improvements (P < 0.05) in BW gain beyond the PC, while the 30 g/ton level equalized feed intake with the PC. Regardless of level, xylanase supplementation improved (P < 0.05) the FCR relative to the NC, thereby equalizing the response with the PC. Similarly, supplementation with any xylanase level increased (P < 0.05) AME over the NC, making all treatments synonymous with the PC. Digesta viscosity of all xylanase-supplemented treatments was decreased relative to both the NC and PC treatments. Overall, this study provided clear evidence that addition of a thermostable xylanase to pelleted wheat-based diets elicited improvements in growth performance of broilers concomitant with a reduction in digesta viscosity and elevation of analyzed dietary AME content.